2014
DOI: 10.18632/oncotarget.1827
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Delta-like 4 (DLL4) promotes renal cell carcinoma hematogenous metastasis

Abstract: The Notch ligand Delta-like 4 (DLL4) plays an important role in tumor angiogenesis, which is required for tumor invasion and metastasis. Here we showed that DLL4 was elevated in endothelium and Notch signaling was activated in renal cell carcinoma (RCC). Exogenous DLL4 induced RCC cell migration and invasion by activating intercellular Notch signaling. Importantly, the DLL4/Notch/Hey1/MMP9 cascades connecting the endothelium to the cancer cells in metastasis were identified. Knockdown of Hey1 decreased express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 32 publications
1
22
0
1
Order By: Relevance
“…Therefore, the expression levels of DLL4, Six1, Notch 1 and Twist 1 were also determined in this study, and the results indicated that HDAC5 increased the expression of DLL4, Six1, Notch 1 and Twist 1 in the A549 cells. Our results were in line with the results from previous studies that found that overexpression of DLL4 was associated with poor outcomes of patients with pancreatic adenocarcinoma, and elevated DLL4 promoted renal carcinoma cell metastasis (26,27). Thus, we may speculate that elevated HDAC5 promotes the expression of DLL4 in lung cancer, and contributes to poor patient outcomes and metastasis.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, the expression levels of DLL4, Six1, Notch 1 and Twist 1 were also determined in this study, and the results indicated that HDAC5 increased the expression of DLL4, Six1, Notch 1 and Twist 1 in the A549 cells. Our results were in line with the results from previous studies that found that overexpression of DLL4 was associated with poor outcomes of patients with pancreatic adenocarcinoma, and elevated DLL4 promoted renal carcinoma cell metastasis (26,27). Thus, we may speculate that elevated HDAC5 promotes the expression of DLL4 in lung cancer, and contributes to poor patient outcomes and metastasis.…”
Section: Discussionsupporting
confidence: 92%
“…1E). Moreover, previous study reported that DLL4 could promote RCC cell migration and invasion by activating intercellular Notch signaling 31 . Data in the UALCAN database revealed that mRNA expression of DLL4 were significantly higher in RCC tissues than in normal tissues in pan-cancer analysis ( Supplementary Fig.…”
Section: B Cells Induced Hif-2α Upregulation Activated Dll4 To Initiamentioning
confidence: 97%
“…Western blot assays were performed as previously described (19). The information on all primary antibodies is listed in Supplementary Table S1.…”
Section: Western Blot Assaymentioning
confidence: 99%